Approaches to Creation of Cryoprotective Media for Cryopreservation of Avian Sperm - Linnik, T. P.; Martynyuk, I. N. (Problems of Cryobiology and Cryomedicine, 2010)
A review of the literature and our own studies of the composition and physico-chemical properties of the cryoprotective media during cryopreservation of avian sperm is presented. Basic principle of forming media from components that perform specific functions in a cycle of freeze-thawing is proposed. We discuss the positive role of inclusion in the composition of the medium of protein supplements instead of lipids (egg yolk). We consider the prospects of complex compositions of cryoprotectants on the basis of diols and amides in combination with non-invasive water-soluble polymers. There are proposed rules of making a mixture of cryoprotectants based on the reduction of their cytotoxicity, the rate and mechanisms of their permeability through the membrane of spermatozoa, the impact on the processes of extra- and intracellular crystallization of osmotically active water.